Strategi Digitalisasi Pasar Rakyat untuk Mendukung Smart Economy: Studi Kasus Kota Banda Aceh (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2026)
The transformation of Banda Aceh into a smart city requires strengthening an inclusive digital economy sector based on local potential. One important aspect of the smart economy is the revitalization of traditional markets so that they can be integrated into the digital economy system. The objective of this study is to formulate a concept for developing a smart market that can adaptively integrate micro, small, and medium enterprises (MSMEs) and traditional markets into the digital ecosystem. This study uses a qualitative descriptive method, supplemented with secondary quantitative data from relevant agencies, such as the number of traders, active market units, and consumer households. The analysis was conducted in three stages: mapping local economic potential, identifying barriers, and designing a user-centered system. The research findings reveal that Banda Aceh has significant local economic potential, with over 1,115 vendors spread across five main markets and more than 64,709 households as active consumers. However, digital integration has not been optimized, marked by low digital literacy among traders, insufficient utilization of platforms such as E-Pasar and Banda Pay, and the absence of a specialized integrated application for market management. This study proposes two development models: (1) an e-commerce system for SMEs that have adapted to technology, and (2) an admin-based service system to support conventional traders. These models are expected to build an inclusive, productive, and competitive digital market ecosystem, supported by strategic policies, digital infrastructure, and cross-sector collaboration.